Peran Budaya Organisasi dalam Mendorong Motivasi Belajar Siswa: Studi Kasus di SMK Negeri 5 Bone - Zatira, Wann (Dimar Jaya Publishing, 2024)
The study aims to determine the role of organizational culture in encouraging student learning motivation at SMK Negeri 5 Bone. This study uses qualitative research with a management approach. Data were collected through observation, interviews, and documentation. The data obtained were then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are three roles of organizational culture in encouraging student learning motivation at SMK Negeri 5 Bone, namely (1) The role of organizational culture, which consists of cultural values, norms, and organizational cultural habits, has an impact on school achievement. (2) Motivation, both intrinsic and extrinsic, plays an important role in shaping students' learning attitudes and behavior. Teachers emphasize that intrinsic motivation provides a strong drive, making students more enthusiastic and persistent in facing learning challenges. Extrinsic rewards, such as praise or physical gifts, can encourage student motivation. (3) The application of positive culture, learning culture, as well as social support and collaboration as the role of organizational culture in encouraging student learning motivation